Aging as an allostasis condition of hormones secretion: summing up the endocrine data from the inChianti study - Valenti, Giorgio (Acta Biomedica Atenei Parmensis, 2010)
Aging phenomena can be seen as a breakdown of the intercellular organisation mechanisms like those represented by endocrine secretions. Such hypothesis is decidedly supported by the analysis of endocrine data coming out from the epidemiological inChianti study. Among the age related endocrine changes a leading role is played by the decline of hormones capable of anabolic effect like Testosterone, IGF-1, DHEAS on the one hand and on the other hand by the even slight increase of the hormones capable of catabolic activity like Cortisol and thyroid hormones. The derangement of this endocrine equilibrium that can be defined with the term of “allostasis”, when chronically protracted, might be seen as responsible for many aging phenomena. Consequently specific hormone supplementations might be suggested as a proper strategy to counteract the functional declines occurring in the last decades of life. Nevertheless clinical intervention trials are mandatory in order to validate the hypothesis and to properly verify the risk/benefit ratio.